Representasi Pornografi Dalam Film Jan Dara - Fathul Nia; Redi Panuju (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2018)
Film is an audio visual communication media to convey a certain message. So most of the movies show a presence in a drama movie can be seen from how women are positioned and represented. The drama film that was studied and analyzed was a movie titled Jan dara. According to laura mulvey cinematic techniques construct a woman as an object of desire and a view for the people behind the screen as well as the audience by highlighting the representation of the female body shape as the main side of sexuality for the object of visual pleasure. In this case cinematic techniques were analyzed which were used in various angles of camera gaze, lighting. So from the analysis results known that cinematic techniques both shooting and lighting techniques in order to be used to launch the desire to look at men and exploit the body of the woman for visual pleasure